Efficient plant regeneration through callus in Zanthoxylum armatum DC: an endangered medicinal plant of the Indian Himalayan region. (3rd May 2020) - Purohit, Sumit; Joshi, Kuldeep; Rawat, Vivek; Bhatt, Indra D.; Nandi, Shyamal K.
Abstract: An efficient in vitro propagation protocol for Zanthoxylum armatum DC has been developed via indirect organogenesis using aseptic leaf explants. The explants were soaked for different time duration (12, 24 or 36 h) in liquid woody plant medium (WPM) supplemented with various concentrations (15.0, 25.0 or 50.0 μM) of thidiazuron (TDZ). The pre-exposed explants transferred for callus induction onto WPM supplemented with different concentrations of TDZ (2.0, 4.0, 6.0, 8.0 and 10.0 μM) either alone or in combination with varied concentrations (0.5, 1 and 1.5 μM) of naphthaleneacetic acid (NAA). Of the tested concentrations and combinations, best response for pretreated (15 μM TDZ for 24 h) explants was achieved on WPM augmented with 6.0 μM TDZ and 0.5 μM NAA after 8 weeks of incubation. For shoot induction, the callus clumps were excised into small pieces (∼0.5 g) and were transferred onto WPM fortified with different concentrations (2.0–9.0 μM) of benzylaminopurine (BA), indole-3-acetic acid (IAA, 1.0 μM) and gibberellic acid (GA3, 0.5–3.0 μM). Maximum shoot number (10.4 ± 0.74) and average shoot length (4.75 ± 0.71 cm) were observed in WPM enriched with 2.0 μM BAP, 1.0 μM IAA and 1.5 μM GA3 after 8 weeks of incubation. The developed shoots (4 cm) were excised, pulse-treated for 24 h in half-strength WPM containing indole-3-butyric acid (IBA, 50.0 μM) prior to their transfer on hormone-free MS medium, where 100% rooting was achieved. The regenerated plants were implanted in soil-filled poly bags, acclimatized properly and subsequently placed under sunlight with 80% survival rate after 60 days recorded. This is the first report for propagation of Z. armatum via callus phase with high rate of shoot proliferation and can be effectively utilized for generating sufficient planting material in promoting its re-cultivation and conservation programme.